The Efficacy of Tocilizumab in the Treatment of Patients with Refractory Immune-Mediated Necrotizing Myopathies: An Open-Label Pilot Study - Li, Sizhao; Li, Wenli; Jiang, Wei; He, Linrong; Peng, Qinglin; Wang, Guochun; Lu, Xin (Frontiers in Pharmacology, 2021)
Objective: To evaluate the efficacy of tocilizumab (TCZ) in adult patients with refractory immune-mediated necrotizing myopathies (IMNMs) and investigate possible predictive biomarkers of the response to treatment with TCZ. Methods: Patients with refractory IMNM were enrolled in this open-label pilot observational study and received intravenous TCZ treatment. The clinical response was assessed after 6 months of TCZ treatment according to the 2016 American College of Rheumatology–European League Against Rheumatism (ACR–EULAR) response criteria for adult dermatomyositis and polymyositis. Muscle biopsies were performed to investigate muscle fiber regeneration by immunohistochemical staining of CD56. Serum levels of interleukin (IL)-6 were measured using a multiplex bead-based flow fluorescent immunoassay. The levels of muscle IL-6 mRNA were detected by real-time polymerase chain reaction. Results: A total of 11 patients with refractory IMNM were enrolled in the study, including 3 anti-3-hydroxy-3-methylglutaryl-CoA reductase- and 8 anti-signal recognition particle-positive patients. Seven (63.6%) of these patients achieved clinically significant responses according to the 2016 ACR–EULAR myositis response criteria. Responders had higher baseline serum IL-6 and muscle IL-6 mRNA levels and percentage of CD56-positive muscle fibers than non-responders. Baseline serum IL-6 levels and the percentage of CD56-positive muscle fibers were positively correlated with total improvement score after 6 months of TCZ treatment. Furthermore, muscle fiber necrosis and muscle fiber size variation decreased in repeated muscle biopsies in five responders. Conclusion: Patients with refractory IMNM may respond to TCZ. Baseline serum IL-6 and muscle IL-6 mRNA levels and the percentage of CD56-positive muscle fibers may predict the response to TCZ treatment in these patients.